Peran Guru PAI dalam Menguatkan Moderasi Beragama di SMK PGRI 2 Ponorogo - Yushima Ifatus Sa’diyah (Al-Abshor : Jurnal Pendidikan Agama Islam, 2025)
This research aims to: (1) Describe the role of Islamic Education (PAI) teachers as educators in strengthening religious moderation at SMK PGRI 2 Ponorogo, (2) Describe the role of PAI teachers as leaders in strengthening religious moderation at SMK PGRI 2 Ponorogo, (3) Describe the role of PAI teachers as evaluators in strengthening religious moderation at SMK PGRI 2 Ponorogo. This study uses a qualitative approach with descriptive research type. To collect data, researchers applied three techniques: interviews, observation, and documentation. The results of this study indicate that as educators, leaders, and evaluators, PAI teachers strive to create an inclusive environment that respects differences. As educators, PAI teachers implement the habit of greeting and communicating in a friendly language to all students regardless of religion, become role models in performing worship, and provide advice without imposing religion. In their teaching, they give warnings and options to leave the class for non-Muslims when discussing sensitive material. As leaders, PAI teachers cultivate the practice of Islamic teachings through religious activities by inviting without coercion and involving non-Muslims as observers. As evaluators, PAI teachers collaborate with other religious leaders in preparing assignments and assessments for non-Muslims, provide fair feedback, and offer remedial lessons for those in need. Abstrak Penelitian ini bertujuan untuk: (1) Mendeskrpsikan peran guru PAI sebagai educator dalam menguatkan moderasi beragama di SMK PGRI 2 Ponorogo, (2) Mendeskrpsikan peran guru PAI sebagai leader dalam menguatkan moderasi beragama di SMK PGRI 2 Ponorogo. (3) Mendeskripsikan peran guru PAI sebagai evaluator dalam menguatkan moderasi beragama di SMK PGRI 2 Ponorogo. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Untuk mengumpulkan data, peneliti menerapkan tiga teknik, yaitu wawancara, observasi, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa sebagai educator, leader, dan evaluator, Guru PAI berupaya menciptakan lingkungan yang inklusif dan menghargai perbedaan.Sebagai educator, Guru PAI menerapkan kebiasaan menyapa dan berkomunikasi dengan bahasa yang ramah kepada semua siswa tanpa membedakan agama, menjadi teladan dalam menjalankan ibadah, dan memberikan nasehat tanpa memaksakan agama. Dalam pengajarannya, guru PAI memberikan peringatan dan pilihan keluar kelas bagi non-Muslim saat pembahasan materi yang sensitif. Sebagai leader, Guru PAI membudayakan pengamalan ajaran Islam melalui kegiatan keagamaan dengan mengajak tanpa paksaan dan melibatkan non-Muslim sebagai pengamat. Sebagai evaluator, Guru PAI menjalin kerja sama dengan pemuka agama lain dalam menyusun tugas dan penilaian bagi non-Muslim, memberikan umpan balik yang adil, dan memberikan remidi bagi yang membutuhkan.